PENGARUH PENGELOLAAN ANGGARAN TERHADAP KINERJA ORGANISASI PEMERINTAHAAN - Ruivo Barros Magno; Abdul Hakim; Tjahjanulin Domai (Universitas Tribhuwana Tunggadewi, 2015)
The objective of research is to investigate the influence of budget management on work performance of government organization in the public sector organization. Research also attempts to examine whether budget management is influential to the performance of public sector. Data are collected through survey with questionnaire. The collected data are processed using SPSS Version 18 to attest whether there is direct and indirect influence of budget management on the performance of public sector organization.Research population is the staffs at The Office of Administration in Ainaro Regency. Questionnaire is given to 35 respondents. The analysis technique is simple regression analysis supported by the software of Statistical Product and Service Solution (SPSS Version 18) that is considered as helpful in data analysis. Independent variable is budget management (X) whereas dependent variable is organizational performance (Y). Before hypothesis testing, the testing instrument is examined through validity test and reliability test. Result of research indicates that there is a direct influence of budget management on organizational performance. The result of current research is supporting previous research and it has been considered as aligning with budget theory and public sector performance.